2000
DOI: 10.1086/516411
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Model of Client Participation in Intensive Family Preservation Services

Abstract: We identify two distinct components of parent participation in intensive family preservation services: collaboration in treatment planning and compliance with program expectations. Using hierarchical linear models, we explore influences on collaboration and compliance at the case, worker, and program levels. Effects of cross-level interactions are also examined. Parental substance abuse, mental health problems, minority status, and lack of extended family support predict lower levels of participation. Workers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 30 publications
3
86
0
2
Order By: Relevance
“…This finding is important as a balance needs to be struck between concrete and therapeutic services (Maluccio et al, 2002:154), as families cannot be expected to develop relationship skills and to manage behavioural problems in the midst of environmental stressors such as a lack of food, clothes and other means of existence (Berry, 1997:145;Cash & Berry, 2001:4;Maluccio et al, 2002:153), as concrete support provides a solution to the daily survival problems (Mullins et al, 2011). It further seems that, according to certain studies (Littell & Tajima;2000:426,428;Mullins et al, 2011), participation by parents is greater when a wide range of concrete services and intercession (mediation) by social workers are available. For example, Ryan and Schuerman (2004:362) found that concrete services such as providing clothes and other supplies decreased the risk of subsequent child abuse in families where there were financial problems.…”
Section:  Accompanying Family Members To Resourcesmentioning
confidence: 99%
“…This finding is important as a balance needs to be struck between concrete and therapeutic services (Maluccio et al, 2002:154), as families cannot be expected to develop relationship skills and to manage behavioural problems in the midst of environmental stressors such as a lack of food, clothes and other means of existence (Berry, 1997:145;Cash & Berry, 2001:4;Maluccio et al, 2002:153), as concrete support provides a solution to the daily survival problems (Mullins et al, 2011). It further seems that, according to certain studies (Littell & Tajima;2000:426,428;Mullins et al, 2011), participation by parents is greater when a wide range of concrete services and intercession (mediation) by social workers are available. For example, Ryan and Schuerman (2004:362) found that concrete services such as providing clothes and other supplies decreased the risk of subsequent child abuse in families where there were financial problems.…”
Section:  Accompanying Family Members To Resourcesmentioning
confidence: 99%
“…In contrast, stronger caseworker effects were found in a study of caregiver compliance in home-based child welfare services (Littell & Tajima, 2000) and in relation to outcomes of brief motivational interventions (Burke, Arkowitz & Dunn, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Interventions aimed at enhancing client motivation (e.g., Miller & Rollnick, 2002) are of great interest, but have not been systematically studied in child welfare settings. One study showed that caseworker and service characteristics were associated with systematic variations in client participation in child welfare in-home services; specifically, caseworkers' child welfare experience, caseload size, and intensity of contact with families related to variations in caregiver compliance (Littell & Tajima, 2000). It is possible that these factors affect caregiver problem recognition and intentions to change.…”
Section: Readiness For Changementioning
confidence: 99%
“…In a review, mindfulness has been shown to buffer against maladaptive behaviors and, instead, replace these behaviors with controlled coping responses (Weinstein, Brown, & Ryan, 2009). In addition, because experiencing adversity may result in avoidant-related behaviors subsequently impacting parent participation in treatment (Littell, Alexander, & Reynolds, 2001;Littell & Tajima, 2000), promoting acceptance and awareness through mindfulness may also positively affect parents' engagement in child welfare services more broadly. Prior research demonstrates that mindfulness-based interventions are effective in reducing stress (Carlson, Speca, Patel, & Goodey, 2004;Williams, Kolar, Reger, & Pearson, 2001), trauma symptoms (Kimbrough et al, 2010;King et al, 2013), and substance misuse (Bowen et al, 2009), as well as improving parent-child interactions (Duncan, Coatsworth, & Greenberg, 2009a).…”
mentioning
confidence: 99%